Emotional Intelligence in management and leadership literature – a bibliometric analysis - Campos, Susana (2020)
Several organizations value technical competences of their employees, but it is not enough to differentiate them. So, market distinguishes organizational staff with social and behavioural skills, such emotional intelligence, to improve organizational performance. During the recent years, emotional intelligence has gained a great relevance in terms of management and leadership research, in different contexts. This research aims to provide a literature review about emotional intelligence in management and leadership context and identify suggestions for future research. To achieve that purpose, we used a bibliometric analysis methodology, specifically a co-citation analysis, with support of VOSviewer software. The articles used in this research were obtained from Web of Science database and published between 1980 and 2018. As main contributions of this study, we intend to identify the emotional intelligence clusters that result of management and leadership literature, make aware researchers and managers to this subject relevance, and show the research trends about the emotional intelligence as basis for a set of soft skills that improve the individual and organizational performance.